Polymorphisms in genes of the BAFF/APRIL system may constitute risk factors of B‐CLL – a preliminary study on a Polish population. Issue 4 (13th August 2015) - Jasek, M.; Wagner, M.; Sobczynski, M.; Wolowiec, D.; Kuliczkowski, K.; Woszczyk, D.; Kielbinski, M.; Kusnierczyk, P.; Frydecka, I.; Karabon, L.
Abstract The association of single‐nucleotide polymorphisms (SNPs) of B‐cell activating factor (BAFF)/a proliferation‐inducing ligand (APRIL) system with B‐cell chronic lymphocytic leukemia (B‐CLL) have been suggested, therefore, we investigated 20 SNPs of BAFF, APRIL, BAFF‐R, transmembrane activator and calcium modulator and cyclophilin‐ligand interactor (TACI), B‐cell maturation antigen (BCMA) genes and the risk and outcome of B‐CLL in 187 patients and 296 healthy subjects as well as ligand‐receptor gene × gene interactions. Although the obtained P‐values for all 20 SNPs did not reach statistical significance for this study (α = 0.003), the high value of the global chi‐squared statistic (χ2df = 38 = 52.65; P = 0.0586), and obtained values of odds ratio indicate that rs9514828 (BAFF), rs3803800 (APRIL) and rs4985726 (TACI) may be associated with the risk of B‐CLL. We observed that the B‐CLL patients with the genotype rs9514828CT/rs11570136AA were diagnosed with the disease 12 years later than the whole group of patients in this study.